Penguatan Keterampilan Berkomunikasi Sosial Siswa dalam Membangun Interaksi Positif di SMAN 1 Sindangwangi Kabupaten Majalengka - Purnama, Gea Indah; Puspitasari, Ratna; Sumarna, Cecep (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
This study aims to explore the description, factors, and efforts made by teachers to strengthen the social communication skills of class XII students of SMAN 1 Sindangwangi, Majalengka Regency. The problem found is the decline in communication skills in students caused by the influence of online game, self-confidence, and the social environment at school. The research method used is a qualitative method with the Alfred Schutz phenomenological approach with the lifeworld experienced by students as research subjects with the intersubjectivity of their positive interactions with other students and teachers. The findings of this study reveal the meaning that students' social communication skills in high school are not only in techniques but are firmly embedded in local Sundanese cultural values, the spirit of collectivity and aspects of religiosity shown through a series of efforts that have been made by teachers, namely implementing varied learning methods including group discussions, presentations, and questions and answers. Teachers also often use PBL and Inquiry Learning models. Teachers have integrated 21st-century skills into learning as an effort to foster intersubjectivity. Prominent factors influencing the social communication skills of 12th-grade students are self-confidence, emotional intelligence, and technology.